Response of soil bacterial community to biochar application in a boreal pine forest - Ge, Yan; Li, Xiao-li; Palviainen, Marjo; Zhou, Xuan; Heinonsalo, Jussi; Berninger, Frank; Pumpanen, Jukka; Köster, Kajar; Sun, Hui (Journal of forestry research, 2023)
Boreal forests commonly suffer from nitrogen deficiency due to low rate of nitrogen mineralization. Biochar may promote soil organic matter decomposition and accelerate nitrogen mineralization. In this study, Illumina NovaSeq sequencing combined with functional annotation of prokaryotic taxa (FAPROTAX) analysis was used to investigate the effect of biochar pyrolysis temperatures, the amount of applied biochar, and the period since the biochar application (2- and 3-year) on soil bacterial communities. The results show that biochar pyrolysis temperatures (500 °C and 650 °C) and the amount of applied biochar (0.5 kg m −2 and 1.0 kg m −2 ) did not change soil properties. Nevertheless, the interaction of biochar pyrolysis temperature and the amount had significant effects on bacterial species richness and evenness ( P < 0.05). The application of biochar produced at 500 °C had a lower abundance of Actinobacteria and Verrucomicrobia, while that produced at 650 °C had a higher abundance of Conexibacter and Phenylobacterium. When biochar produced at 650 °C was applied, applying 0.5 kg m −2 had a higher abundance of Cyanobacteria , Conexibacter , and Phenylobacterium than that of 1.0 kg m −2 ( P < 0.05). Functionally, the abundance of the aromatic compound degradation group increased with the extension of application time and increase of pyrolysis temperature. The time since application played an important role in the formation of soil bacterial communities and their functional structure. Long-term studies are necessary to understand the consequence of biochar on bacterial communities in boreal forests.